2018
DOI: 10.1080/01616412.2018.1544385
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of Glutathione S-transferase omega-1 and omega-2 genetic polymorphisms and ischemic stroke risk in a Turkish population

Abstract: , 131 pages Stroke is defined as the acute neurological cerebrovascular disease based on interruptions to blood flow in the brain. These interruptions are caused by loss of blood supply due to vessel bursts or vessel blocked by clotting. Atherosclerosis, a main cause of stroke, is blockage of endothelium layer of arteries and losing the flexibility of tissue. The oxidative stress is known as a risk factor for atherosclerosis. The increased free radicals such as reactive oxygen species (ROS) and decreased antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In addition, these GCLC and GCLM gene polymorphisms showed statistically significant associations with an increased risk of myocardial infarction and endothelial dysfunction [53,54]. Much more often, the objects of genetic association studies in ischemic stroke were polymorphic variants of glutathione-S-transferase genes, which showed associations with disease risk [17,19,21]. Furthermore, in a previous study, we looked at the associations between polymorphisms in glutathione peroxidase genes such as GPX1 (rs1050450), GPX3 (rs2070593), and GPX4 (rs713041) and the risk of cerebral stroke in hypertensive patients, and we observed that SNP rs713041 of the GPX4 gene is associated with an increased risk of stroke [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these GCLC and GCLM gene polymorphisms showed statistically significant associations with an increased risk of myocardial infarction and endothelial dysfunction [53,54]. Much more often, the objects of genetic association studies in ischemic stroke were polymorphic variants of glutathione-S-transferase genes, which showed associations with disease risk [17,19,21]. Furthermore, in a previous study, we looked at the associations between polymorphisms in glutathione peroxidase genes such as GPX1 (rs1050450), GPX3 (rs2070593), and GPX4 (rs713041) and the risk of cerebral stroke in hypertensive patients, and we observed that SNP rs713041 of the GPX4 gene is associated with an increased risk of stroke [23].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have so far investigated the relationship between genes encoding glutathione-metabolizing enzymes and the risk of ischemic stroke and its outcomes. These genetic association studies have been focused on enzymes such as glutathione S-transferases [17][18][19][20][21] and glutathione peroxidases [22,23] that use glutathione as a substrate for the detoxification of foreign compounds and hydrogen peroxide, respectively [19][20][21]23]. No studies have so far been undertaken to investigate the contribution of polymorphic genes involved in glutathione biosynthesis to the development and severity of ischemic stroke, although a deficiency of glutathione in IS patients has been reported by several studies [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that our updated analyses were derived from more eligible studies, our observations should be considered as a valuable confirmation for pre-existing literatures. Fifthly, GST null polymorphisms have also been found to be closely associated with the risk of diabetes, essential hypertension and other types of atherothrombotic disorders such as ischemic stroke or peripheral artery disease [16][17][18][19][20]. Considering that the above mentioned diseases are either considered to be conventional risk factors of CAD or usually manifest as co-morbid conditions of CAD, it would be interesting to perform some stratified analyses accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…As an intracellular thiol tripeptide present in all mammalian tissues, GSH plays a crucial role in cellular protection against oxidant damage. Reduction of the GSH level in vivo may lead to the degeneration of dopaminergic neurons (Li et al, 1997;Cadenas, 2004;Bilgin et al, 2019). Song et al, 2015 reported that intravenous injection of exogenous GSH attenuated cerebral infarct volume after ischemic stroke by promoting the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%